The Structure of Jay Gatsby’s Personality in The Great Gatsby Novel - Ratri, Nindita; Istri Aryani, I Gusti Agung (Humanis; Vol 23 No 1 (2019)DO - 10.24843/JH.2019.v23.i01.p09, 2019)
This study entitled “The Structure of Jay Gatsby’s Personality in The Great Gatsby Novel” is aimed to describe Jay Gatsby’s structure of personality and his behavioral representations. The data were taken from the novelThe Great Gatsby written by F. Scott Fitzgerald. Qualitative method was applied to analyze Jay Gatsby’s structure of personality and his behavioral representations. The theories used to analyzed are the theory of literature proposed by Kenney, theory of psychoanalysis and theory of anxiety proposed by Freud. The theory of literature showed that The Great Gatsby used mixed plot and in order to reveal the character of Jay Gatsby, mixing method was used.The psychoanalysis theory showed three structures of personality of human minds: the id, the ego, and the superego. The behavioral representations of the structure of personality showed in anxiety and defense mechanism of the ego: repression, fixation, and regression. The result of analysis showed that the desire of human beings must not be negative and must be realistic otherwise it will effect his/her behavior and how he/sheis treated in society.